Os sentidos da participação cidadã no PROJOVEM - Programa Nacional de Inclusão de Jovens (2005 2006) - Villas-Bôas, Renata Junqueira Ayres (2008)
This paper analyzes the proposal of community action developed within the National Program for Youth Inclusion (Projovem), a federal government program initiated in 2005, oriented toward at-risk youth between the ages of 18 and 24, whose objectives include the elevation of scholarship, professional training, and education for citizenship. The study focuses on the assumptions and objectives, presented in the political and pedagogic design of the Program, that support the goals of citizenship promotion and youth participation in public life. It looks to reclaim the concepts of participative democracy, citizenship, civil rights, public space, and civil society, as developed by various authors. In addition, the paper analyzes the intersection of these concepts with reflections on youth, youth rights, public policy, and youth participation that have been produced in recent years, comparing it with the community action proposed by Projovem